A review on mechanisms and recent developments of nanomaterials based carbon fiber reinforced composites for enhanced interface performance. Issue 1 (23rd January 2023) - Li, X.; Liu, T.; Lin, P.; Xiang, W.; Shang, H.; Liu, Y.; Zhang, S.
Abstract: Carbon fiber reinforced composites have attracted lots of attention in many fields. However, on account of the poor infiltration of resin to carbon fiber, the weak interface performance between fiber and resin has been restricting the interface properties of composites. In recent progress, the review attaches more importance to the introduction of the third phase monomer, which mainly uses physical and chemical methods to assemble nanomaterials (such as carbon nanotubes, graphene, etc.) on the carbon fiber surface to modify the interface structure of the carbon fiber reinforced composites, and all of them have been demonstrated in this paper. Furthermore, the effects of introducing nanomaterials on the structure of the fiber/resin interface and the relationship between multi‐scale interface structure and properties have been investigated. It can be seen that the design idea of researchers mainly uses one or more theories to improve the interface properties of carbon fiber reinforced composites, such as transition layer, chemical bonding, mechanical interlocking, infiltration, diffusion, and adsorption. In brief, this work provides some novel insights for the preparation of carbon fiber reinforced composites with excellent interlaminar shear strength. Abstract : The effects of preparation method, nanomaterial content and other preparation conditions on interlaminar shear strength enhancement mechanism of nanomaterials based carbon fiber reinforced composites are discussed. And the influence of the introduction of nanomaterials on the fiber/resin interface structure and the relationship between multi‐scale interface structure and performance have been studied.